2021
DOI: 10.1371/journal.pone.0253651
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ attitude on the practice of e-learning: A cross-sectional survey amid COVID-19 in Nepal

Abstract: Introduction In present days, the use of information technology (IT) in education is unquestionable. The mounting advancement of IT has changed the scenario of education. With the emergence of the current COVID-19 situation, it has undoubtedly provided a solution to most of our educational needs when all educational institutions remained closed due to the pandemic. This study aims to identify the nursing students’ attitude towards the practice of e-learning amidst COVID-19. Methods A descriptive web-based cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
105
6
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(157 citation statements)
references
References 25 publications
24
105
6
22
Order By: Relevance
“…There are various obstacles in the online learning that cause the learning process to be less than optimal. Some studies reported that the internet connection and facilities owned by the students and, also tutors were the important factors that become a "barrier" in online learning [7], [23]. It was supported by the additional student perspectives findings of this study which reported that internet connection is an "obstacle," thus, our findings indicate a limitation "barrier."…”
Section: Discussionsupporting
confidence: 79%
“…There are various obstacles in the online learning that cause the learning process to be less than optimal. Some studies reported that the internet connection and facilities owned by the students and, also tutors were the important factors that become a "barrier" in online learning [7], [23]. It was supported by the additional student perspectives findings of this study which reported that internet connection is an "obstacle," thus, our findings indicate a limitation "barrier."…”
Section: Discussionsupporting
confidence: 79%
“…Internet bandwidth and connectivity limitations, technical support limitations, and unfamiliarity with online learning systems were also seen against its implementation in the study by Gismalla et al (2021). Similar reports involving Internet problems, poor connectivity, and technical issues were also brought up by Thapa et al (2021), Gupta et al (2021), Olum et al (2020), Elshami et al (2021), Hayat et al (2021), and Bączek et al (2021). Different network issues were also reported by around one-third of respondents of Singh et al (2021), including troubles with sound and video or unexpectedly being logged out from the classes.…”
Section: Discussionmentioning
confidence: 65%
“…First, educational adaptations during the COVID-19 pandemic have included a shift from face-to-face learning to online or flexible learning paradigms (O'Flynn-Magee et al, 2021;Pokhrel and Chhetri, 2021;Sahu, 2020). Studies have found that students face additional learning challenges when adjusting to these different learning modalities (Dewart et al, 2020;Majrashi et al, 2021;Wallace et al, 2021), including internet problems, technological issues, the absence of experimental/practical classes and reduced interactions with peers and educators (W. Li et al, 2021a;Thapa et al, 2021). Faculty members required more time to prepare for online classes and were forced to learn how to navigate and deliver the course content online (Agu et al, 2021;Almahasees et al, 2021).…”
Section: Discussionmentioning
confidence: 99%